Analisis Pengendalian Kualitas dalam Menjaga Mutu Produk Furniture pada CV Java Teak Furnindo - Damam, Muhammad Khoirul; Yustika, Gaung Perwira (Haka Vyza Media, 2025)
Product Quality Control is a very important process in the manufacturing industry. Good product quality increases consumer satisfaction and improves the company's reputation. This research is motivated by the importance of product quality in the manufacturing industry so that the products produced meet the expected quality so that they meet customer expectations and needs. The purpose of this research was to determine the implementation of Product Quality Control at CV Java Teak Furnindo, what factors influence product quality, and what efforts are made to maintain the quality of furniture products so that their quality is maintained. The research method is qualitative Analysis with a Descriptive Approach. The data collection techniques used are observation and interviews. There are two data sources used, namely Primary Data Sources and Secondary Data Sources.The Primary data source was obtained from CV Java Teak Furnindo as the research object. secondary data sources come from scientific journals, articles and books. The results of this research show that several factors influence product quality, starting from raw materials, human resources, machines and technology, use of quality materials. There are several efforts made to maintain the quality of furniture products, namely by using quality raw materials, monitoring the production process, developing a quality management system, and developing human resources.